RELEVANSI LOGIKA SOSIAL KONSUMSI DENGAN BUDAYA KONSUMERISME DALAM PERSPEKTIF EPISTEMOLOGI JEAN BAUDRILLARD - ., Fadhilah (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45, 2011)
This research is literature study with title Relevance Of The Social Logic of Consumption To The Consumerism Culture In Jean Baudrillard‟s Perspective Epistemology. It aims at describing Jean Baudrillard‟s view of consumption it epistemological perspective, the consumptive society and relevance of the consumption to the consumerism culture in Jean Baudrillard‟s perspective. The systematically reporting of the study results that consist of data analysis using hermeneutics method and induction- deduction methods to draw conclusions of the study object.